2018
DOI: 10.1002/adma.201802991
|View full text |Cite|
|
Sign up to set email alerts
|

Controllable, Wide‐Ranging n‐Doping and p‐Doping of Monolayer Group 6 Transition‐Metal Disulfides and Diselenides

Abstract: Developing processes to controllably dope transition-metal dichalcogenides (TMDs) is critical for optical and electrical applications. Here, molecular reductants and oxidants are introduced onto monolayer TMDs, specifically MoS , WS , MoSe , and WSe . Doping is achieved by exposing the TMD surface to solutions of pentamethylrhodocene dimer as the reductant (n-dopant) and "Magic Blue," [N(C H -p-Br) ]SbCl , as the oxidant (p-dopant). Current-voltage characteristics of field-effect transistors show that, regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 39 publications
5
129
0
Order By: Relevance
“…However, ML films that were grown at 600, 700, and 1000 °C possess much lower electron doping densities. Moreover, Figure g indicates that the reported n el values derived from electronic device drain currents exhibit almost one order of magnitude less than that of PL spectra, which is a recently reported phenomenon . Through analysis of the PL characterization above, we demonstrated that the electron doping level of the wafer‐scale ML MoS 2 film could be engineered by simply varying the experimental parameters in the two‐step growth process.…”
Section: Resultsmentioning
confidence: 68%
See 2 more Smart Citations
“…However, ML films that were grown at 600, 700, and 1000 °C possess much lower electron doping densities. Moreover, Figure g indicates that the reported n el values derived from electronic device drain currents exhibit almost one order of magnitude less than that of PL spectra, which is a recently reported phenomenon . Through analysis of the PL characterization above, we demonstrated that the electron doping level of the wafer‐scale ML MoS 2 film could be engineered by simply varying the experimental parameters in the two‐step growth process.…”
Section: Resultsmentioning
confidence: 68%
“…Figure g provides a comparison of n el values in this work versus previous reports. The red points are the n el values as derived by PL photoexcitation . The black points are the n el values obtained through electronic device drain currents .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While significant research has been dedicated thus far to studying the optical, mechanical, and electrical properties of 2D materials, 3,[5][6][7][8][9] exploring magnetism is still in its infancy, even though 2D magnetic materials provide a solid-state platform to experimentally access fundamental, low-dimensional physics. 10,11 Additionally, any 2D magnetic material would likely still possess the captivating properties of 2D materials, including extremely large mechanical flexibility, 12,13 efficient tuning of transport properties with an electric field, [14][15][16][17] relative ease of chemical modification, 18,19 as well as the ability to create van der Waals stacked heterostructures. 20 These myriad of tuning parameters could unlock opportunities for customengineered magnetoelectric and magneto-optical devices, where 2D magnets coupled with other technologically relevant materials could realize unprecedented capabilities in fields such as spintronics.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been proposed for tuning E F within the band gap of TMDCs, including substitution with dopant atoms 15 , stacking with other 2D materials 16 , exposure to gases [6][7][8]17 , adsorption of alkali metals 18,19 , and adsorption of organic molecules [20][21][22][23][24][25][26] . In accordance with this approach, deposition of molecular electron acceptors or donors on TMDCs has been suggested as a very effective strategy for controlling the E F position via doping, and accordingly high-performance TFTs were realized 22,24,26 . However, the extent to which the changes in electrical TFT characteristics were indeed due to electron transfer between the dopant molecules and the monolayer TMDC (ML-TMDC) was not unambiguously demonstrated, and mostly changes of photoluminescence intensity of excitons versus trions were interpreted as signature of charge transfer (CT).…”
mentioning
confidence: 99%